(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2025)
The results of two years of research on the complex effect of different variants of pre-sowing seed treatment and foliar feeding with different combinations of growth stimulants and complex water-soluble fertilizers on the dynamics of increasing the area of the assimilation surface of sunflower hybrids of different maturity groups are presented.